Studi Mineralogi pada Batuan Sedimen dan Laterit di Daerah Abepantai Kampung Nafri Distrik Abepura, Kota Jayapura, Papua - Adifian Tanga Datu; Endang Hartiningsih; Rahmat Indrajati (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
Minerals are solid objects that can be found in nature, formed inorganically, with chemical composition at certain limits and have atoms arranged regularly. Rocks can be distinguished based on the formation process and mineral content. The purpose of this study is to identify minerals in sedimentary rocks and laterite deposits in this study used analytical methods, namely Binocular Microscope and XRD (X-Ray Diffraction) laboratory tests. XRD analysis is used to determine the type of mineral in the sample. Based on the results of the XRD X-Ray Diffraction lab test, each sample has a different mineral content.